Semi-metal doped Fe-based monatomic catalyst as well as preparation method and application thereof

By doping Sb elements into FeNC single-atom catalysts to form a FeSbNC structure, the problem of insufficient adsorption capacity of Fe-based catalysts to OH* is solved, and the catalyst activity and stability are improved, which is suitable for cathode oxygen reduction reaction of proton exchange membrane fuel cells.

CN119627133AActive Publication Date: 2025-03-14HARBIN INST OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411785535.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing Fe-based single-atom catalyst has a large adsorption energy on OH* in oxygen reduction reaction, which limits the further improvement of its performance.

Method used

By doping the semi-metallic element Sb in the FeNC single atom catalyst, the FeSbNC structure is formed, and the adsorption capacity of the Fe active site is adjusted by using the N-bridged Fe=2N=Sb coordination structure and the hydroxyl group on the Sb atom.

Benefits of technology

The activity and stability of FeSbNC catalysts are significantly improved, the half-wave potential and ultimate current density of the oxygen reduction reaction are improved, the hydrogen peroxide yield is reduced, and the corrosion resistance and reaction kinetics of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627133A_ABST
    Figure CN119627133A_ABST
Patent Text Reader

Abstract

The invention discloses a semi-metal doped Fe-based monatomic catalyst as well as a preparation method and application thereof, relates to a Fe-based monatomic catalyst as well as a preparation method and application thereof, and aims to solve the problem that an iron-based non-noble metal monatomic catalyst is insufficient in activity and stability in an oxygen reduction reaction. According to the catalyst disclosed by the invention, atoms of Fe and Sb form atom pairs and are embedded into a carbon carrier, a Fe = 2N = Sb coordination structure is shown, and meanwhile, a hydroxyl group is formed in the axial direction of the Sb atom. The preparation method comprises the following steps: carrying out heat treatment on ZIF-8 to obtain an N-doped porous carbon material, uniformly mixing the N-doped porous carbon material with Fe salt and Sb salt solutions, drying by distillation, and carrying out heat activation to obtain the catalyst. After the prepared electrode is aged for 30,000 circles in a 0.1 M HClO4 solution, the half-wave potential is only reduced by 18mV. The assembled proton exchange membrane fuel cell has power densities of 1098.3 mW / cm < 2 > and 613.41 mW / cm < 2 > under hydrogen-oxygen and hydrogen-air conditions, and can be used in the field of fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an Fe-based single-atom catalyst and a preparation method thereof, and belongs to the field of preparation of electrocatalysts. Background Art

[0002] Proton exchange membrane fuel cells have attracted much attention as a clean energy conversion device. However, the oxygen reduction reaction at the cathode is slow. The most ideal Pt-based precious metal catalysts currently have low reserves, high costs, are easily poisoned, and have poor stability, which limits their large-scale commercialization. It is crucial to develop highly active, low-cost non-precious metal ORR catalysts. In recent years, research on non-precious metal catalysts has entered the atomic level. Fe-based single-atom catalysts have high oxygen reduction activity, but the adsorption energy of Fe-based single-atom catalysts for OH* is large, which limits their further performance improvement. Summary of the invention

[0003] The present invention aims to solve the technical problem of insufficient catalytic activity and stability of existing Fe-based catalysts and to provide a method for preparing a semi-metal-doped Fe-based single-atom catalyst.

[0004] The semi-metal doped Fe-based single-atom catalyst of the present invention is a pair of atoms of two metals, Fe and Sb, which are embedded in a carbon carrier, wherein Fe and Sb are coordinated with four N atoms respectively, and Fe and Sb share two N atoms, showing an N-bridged Fe=2N=Sb coordination structure, and the Sb atom has a hydroxyl group in the axial direction. The catalyst is recorded as FeSbNC.

[0005] The preparation method of the semi-metal-doped Fe-based single-atom catalyst of the present invention is carried out according to the following steps:

[0006] 1. Preparation of ZIF-8 precursor: First, 2-methylimidazole is uniformly dissolved in a methanol solution to obtain a solution A; then zinc nitrate is dissolved in a methanol solution to obtain a solution B; solution B is added to solution A, stirred at room temperature for 20 to 24 hours, and then centrifuged, washed, and dried to obtain a ZIF-8 precursor;

[0007] 2. Preparation of N-doped porous carbon material: After grinding the ZIF-8 precursor, place it in a tube furnace, heat it to 800-1100°C in an inert atmosphere and keep it for 1-2 hours for heat treatment. After cooling, the N-doped porous carbon material is obtained, which is recorded as NC.

[0008] 3. Preparation of FeSbNC single-atom catalyst: Fe salt, Sb salt and methanol are fully mixed to obtain solution C; then the N-doped porous carbon material and solution C are evenly mixed, heated and stirred in a water bath until the methanol is completely volatilized, and dried to obtain a precursor; then the precursor is placed in a tubular furnace, heated to 900-1100°C under an inert atmosphere and maintained for 0.5-2.5h for thermal activation, and after cooling, a semi-metal-doped Fe-based single-atom catalyst is obtained.

[0009] Furthermore, the molar ratio of 2-methylimidazole to zinc nitrate in step 1 is (2-4):1.

[0010] Furthermore, the stirring speed described in step 1 is 90 to 120 r / min.

[0011] Furthermore, the heating rate of the tubular furnace in step 2 is 2-10° C. / min.

[0012] Furthermore, the iron salt described in step three is ferric chloride, ferric nitrate or ferric acetylacetonate.

[0013] Furthermore, the antimony salt in step three is antimony chloride or antimony nitrate.

[0014] Furthermore, the mass ratio of the antimony salt to the iron salt in step three is (0.5-2):1.

[0015] Furthermore, the mass ratio of the antimony salt to the N-doped porous carbon material in step three is (0.05-0.4):1.

[0016] Furthermore, the water bath heating temperature in step three is 50-70°C.

[0017] Furthermore, the heating rate of the tubular furnace described in step three is 2 to 10° C. / min.

[0018] Furthermore, the drying temperature in steps one and three is 50-70° C., and the drying time is 5-8 hours.

[0019] Furthermore, the inert atmosphere in steps 2 and 3 is Ar or N2.

[0020] The application of the above-mentioned semi-metal-doped Fe-based single-atom catalyst is to use it for the cathode oxygen reduction reaction of a proton exchange membrane fuel cell.

[0021] The present invention uses ZIF-8 as a carrier, adopts a rotary evaporation method to prepare a precursor, and obtains a single-atom catalyst FeSbNC by high-temperature heat treatment. The activity and stability of the obtained catalyst are significantly higher than those of the FeNC single-atom catalyst. Figure 1 shown.

[0022] The beneficial effects of the present invention compared to the prior art are:

[0023] (1) The present invention can reduce the adsorption of OH* intermediates on the Fe active site during the oxygen reduction process by doping the semi-metallic element Sb on the original FeNC single atom catalyst, thereby improving the intrinsic activity of the FeNC single atom catalyst;

[0024] (2) Compared with FeNC single-atom catalysts, the present invention has a higher half-wave potential and limiting current density in acidic electrolytes, a lower hydrogen peroxide yield and a more direct four-electron process, making the carbon matrix more corrosion-resistant. In fuel cell tests, its peak power density exceeds 1 W / cm 2 , which can be used in the field of proton exchange membrane fuel cells.

[0025] (3) The present invention improves the graphitization degree of the carbon matrix and the stability of the catalyst through a two-step heat treatment process. At the same time, the high specific surface area of ​​the carbon matrix provides more active sites for the oxygen reduction reaction, thereby improving the reaction kinetics of the catalyst. The electrode prepared with the semi-metal-doped Fe-based single-atom catalyst of the present invention has a half-wave potential drop of only 18 mV after aging for 30,000 cycles in a 0.1M HClO4 solution. The assembled proton exchange membrane fuel cell has a peak power density of 1098.3 mW / cm under hydrogen and oxygen test conditions. 2 , the peak power density under hydrogen-air test conditions reached 613.41mW / cm 2 , which can be used in the field of fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a flow chart for preparing the semi-metal-doped Fe-based single-atom catalyst of the present invention;

[0027] Figure 2 is a SEM image of the FeSbNC single-atom catalyst prepared in Example 1;

[0028] Figure 3 is a TEM image of the FeSbNC single atom catalyst prepared in Example 1;

[0029] Figure 4 is a spherical aberration electron microscope image of the FeSbNC single-atom catalyst prepared in Example 1;

[0030] Figure 5 is an EDS surface scanning image of the FeSbNC single atom catalyst prepared in Example 1;

[0031] Figure 6 is a schematic structural diagram of the FeSbNC single-atom catalyst prepared in Example 1;

[0032] Figure 7are XRD spectra of the FeSbNC single atom catalyst prepared in Example 1, the FeNC single atom catalyst prepared in Comparative Example 1, and the SbNC single atom catalyst prepared in Comparative Example 2;

[0033] Figure 8 are Raman images of the FeSbNC single atom catalyst prepared in Example 1, the FeNC single atom catalyst prepared in Comparative Example 1, and the SbNC single atom catalyst prepared in Comparative Example 2;

[0034] Fig. 9 are ORR polarization diagrams of the FeSbNC single atom catalyst prepared in Example 1, the FeNC single atom catalyst prepared in Comparative Example 1, and the SbNC single atom catalyst prepared in Comparative Example 2;

[0035] Fig.10 is the ORR polarization diagram of the FeSbNC single atom catalyst prepared in Example 1 before and after aging;

[0036] Fig.11 is the ORR polarization diagram of the FeNC single atom catalyst prepared in Comparative Example 1 before and after aging;

[0037] Fig.12 This is a performance comparison chart of the FeSbNC single-atom catalyst prepared in Example 1 in a fuel cell test. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0039] Example 1: The preparation method of the semi-metal-doped Fe-based single-atom catalyst of this example is carried out according to the following steps:

[0040] 1. Preparation of ZIF-8 precursor: First, 19.275g of 2-methylimidazole was uniformly dissolved in 500ml of methanol solution to obtain solution A; then 24g of zinc nitrate was dissolved in 500ml of methanol solution to obtain solution B; solution B was poured into solution A, and vigorously stirred at 100r / min for 24h at room temperature of 24°C, then centrifuged, washed, and then dried in an oven at a temperature of 60°C for 7h to obtain ZIF-8 precursor;

[0041] 2. Preparation of N-doped porous carbon materials: After grinding the ZIF-8 precursor, place it in a tube furnace, heat it to 1000°C at 5°C / min in an Ar atmosphere and keep it for 1.5h for heat treatment. After cooling to room temperature, N-doped porous carbon materials are obtained, which are recorded as NC.

[0042] 3. Preparation of FeSbNC single atom catalyst: 20 mg of ferric nitrate, 20 mg of antimony chloride and 60 ml of methanol were fully mixed to obtain solution C; then 120 mg of N-doped porous carbon material was fully mixed with solution C, heated and stirred in a water bath at 60°C until the methanol was completely volatilized, and then placed in an oven at 60°C for 7 hours to obtain a precursor; then the precursor was placed in a tubular furnace, and in an Ar atmosphere, the temperature was raised to 1000°C at 5°C / min and maintained for 1 hour. After cooling, a semi-metal-doped Fe-based single atom catalyst was obtained, which was recorded as FeSbNC.

[0043] Example 1 Preparation of FeSbNC single-atom catalyst SEM photos as shown Figure 2 As shown in the TEM images Figure 3 shown; from Figure 2 and Figure 3 It can be seen that the FeSbNC single-atom catalyst particles are dodecahedral with uniform morphology and a particle size of 100 to 200 nm.

[0044] The spherical aberration electron microscopy image of the FeSbNC single-atom catalyst prepared in Example 1 is as follows: Figure 4 As shown, the EDS surface scan image is shown in Figure 5; Figure 4 and Figure 5 It can be seen that there are no metal particles or clusters in the FeSbNC single-atom catalyst, and the Fe and Sb atoms are dispersed at the atomic level.

[0045] The schematic diagram of the structure of the FeSbNC single-atom catalyst prepared in Example 1 is as follows Figure 6 As shown; the brown balls are C, the gray balls are N, the yellow balls are Fe, the brown balls are Sb, the red balls are O, and the pink balls are H. The atoms of the two metals Fe and Sb form atomic pairs and are embedded in the carbon support, where Fe and Sb are coordinated with 4 N respectively, and Fe and Sb share two N, showing an N-bridged Fe=2N=Sb coordination structure. At the same time, there is an -OH group on the axial direction of the Sb atom, and Sb plays a regulatory role on the Fe active site.

[0046] Comparative Example 1: In this comparative example, FeNC single-atom catalyst was prepared, and the specific method was as follows:

[0047] 1. Preparation of ZIF-8: First, 19.275 g of 2-methylimidazole was uniformly dissolved in 500 ml of methanol solution to obtain solution A; then 24 g of zinc nitrate was dissolved in 500 ml of methanol solution to obtain solution B; solution B was poured into solution A, and vigorously stirred at 100 r / min for 24 h at room temperature of 23 ° C, then centrifuged and washed, and then placed in an oven at a temperature of 60 ° C for 7 h to obtain a ZIF-8 precursor;

[0048] 2. Preparation of NC: After grinding the ZIF-8 precursor, place it in a tube furnace, heat it to 1000°C at 5°C / min in an Ar atmosphere and keep it for 1.5h. After cooling, the N-doped porous carbon material is obtained;

[0049] 3. Preparation of FeNC single-atom catalyst: 20 mg of ferric nitrate was fully mixed with 60 ml of methanol to obtain solution C; then 120 mg of N-doped porous carbon material was fully mixed with solution C, heated in a 60°C water bath with stirring until the methanol was completely volatilized, and then dried in an oven at 60°C for 7 h to obtain a Fe precursor; the Fe precursor was placed in a tubular furnace, and in an Ar atmosphere, the temperature was increased to 1000°C at 5°C / min and maintained for 1 h. After cooling, a FeNC single-atom catalyst was obtained.

[0050] Comparative Example 2: In this comparative example, SbNC single-atom catalyst was prepared, and the specific method was carried out according to the following steps:

[0051] 1. Preparation of ZIF-8: 19.275 g of 2-methylimidazole was uniformly dissolved in 500 ml of methanol solution to obtain solution A; 24 g of zinc nitrate was dissolved in 500 ml of methanol solution to obtain solution B; solution B was poured into solution A, and vigorously stirred at a speed of 100 r / min at room temperature of 23°C for 24 h, then centrifuged, washed, and then dried in an oven at a temperature of 60°C for 7 h to obtain a ZIF-8 precursor;

[0052] 2. Preparation of NC: After grinding the ZIF-8 precursor, place it in a tube furnace, heat it to 1000°C at 5°C / min in an Ar atmosphere and keep it for 1.5h. After cooling, N-doped porous carbon material is obtained;

[0053] 3. Preparation of SbNC single atom catalyst: 20 mg of antimony chloride was fully mixed with 60 ml of methanol to obtain solution C; then 120 mg of N-doped porous carbon material was fully mixed with solution C, heated in a water bath at 60°C with stirring until the methanol was completely volatilized, and dried in an oven at 60°C for 7 h to obtain Sb precursor; then the Sb precursor was placed in a tubular furnace, and in an Ar atmosphere, the temperature was raised to 1000°C at 5°C / min and maintained for 1 h, and after cooling, the SbNC single atom catalyst was obtained.

[0054] The XRD spectra of the FeSbNC single atom catalyst prepared in Example 1, the FeNC single atom catalyst prepared in Comparative Example 1, and the SbNC single atom catalyst prepared in Comparative Example 2 are shown in FIG. Figure 7 As shown, from Figure 7It can be seen that only the diffraction peaks of graphite carbon appear at 26.8° and 42°, and no sharp metal peaks appear, which proves that the FeSbNC single atom catalyst prepared in Example 1, the FeNC single atom catalyst prepared in Comparative Example 1, and the SbNC single atom catalyst prepared in Comparative Example 2 do not have the presence of metal particles or clusters, verifying their atomic-level dispersion.

[0055] The Raman spectra of the FeSbNC single atom catalyst prepared in Example 1, the FeNC single atom catalyst prepared in Comparative Example 1, and the SbNC single atom catalyst prepared in Comparative Example 2 are shown in FIG. Figure 8 As shown, the FeSbNC single-atom catalyst prepared in Example 1 is compared with the FeNC single-atom catalyst prepared in Comparative Example 1. D / I G It indicates that the addition of Sb element increases the graphitization degree of the catalyst, thereby improving the stability of the catalyst.

[0056] The ORR activity of the FeSbNC single-atom catalyst prepared in Example 1, the FeNC single-atom catalyst prepared in Comparative Example 1, and the SbNC single-atom catalyst prepared in Comparative Example 2 was tested by step voltammetry (SCV). In an oxygen-saturated 0.1M HClO4 solution, the potential range was 1.0-0.1V, with a step of 0.05V, and a time interval of 30 seconds between each step. The speed of the RRDE rotating disk electrode was 900rpm. The obtained ORR polarization diagram is shown in Figure 2. Fig. 9 As shown, from Fig. 9 It can be seen that in 0.1M HClO4 solution, compared with FeNC single atom catalyst, FeSbNC single atom catalyst has a higher half-wave potential and a larger limiting current density.

[0057] The FeSbNC single-atom catalyst prepared in Example 1 was subjected to an accelerated aging test. Cyclic voltammetry was performed in an oxygen-saturated electrolyte solution with a scanning potential range of 0.6 to 1.0 V (vs. RHE) and a scanning rate of 200 mV / s. The ORR polarization diagram of the FeSbNC single-atom catalyst prepared in Example 1 before and after aging is shown in FIG. Fig.10 As shown, from Fig.10 It can be seen that after aging for 30,000 cycles in 0.1M HClO4 solution, the half-wave potential of the FeSbNC single-atom catalyst only dropped by 18 mV. Under the same conditions, the FeNC single-atom catalyst prepared in Comparative Example 1 was subjected to an accelerated aging test. The ORR polarization diagrams of the FeNC single-atom catalyst prepared in Comparative Example 1 before and after aging are shown in Figure 2. Fig.11 As shown, from Fig.11It can be seen that after aging for 30,000 cycles in 0.1M HClO4 solution, the half-wave potential of the FeSbNC single-atom catalyst decreased by 33 mV, indicating that the FeSbNC single-atom catalyst prepared in Example 1 has better stability than the FeNC single-atom catalyst.

[0058] The FeSbNC single-atom catalyst prepared in Example 1 was brush-coated to a loading of 2 mg / cm 2 The cathode is 0.1 mg / cm 2 The Pt catalyst with the highest loading was used to assemble the fuel cell. The anode test gas was air and oxygen (flow rate 2 ml / min), and the cathode test gas was hydrogen (flow rate 0.5 ml / min). The battery polarization curve and power density performance test were performed. The performance comparison chart in the fuel cell test is shown in the figure below. Fig.12 As shown in Figure 2, the peak power density of FeSbNC single-atom catalyst in proton exchange membrane fuel cell under hydrogen and oxygen test conditions reached 1098.3 mW / cm 2 , the peak power density under hydrogen-air test conditions reached 613.41mW / cm 2 . It has high practical value.

Claims

1. A semi-metal-doped Fe-based single-atom catalyst, characterized in that The catalyst is formed by atoms of two metals, Fe and Sb, forming atomic pairs and embedded in a carbon carrier, wherein Fe and Sb are coordinated with four N atoms respectively, and Fe and Sb share two N atoms, showing an N-bridged Fe=2N=Sb coordination structure. At the same time, there is a hydroxyl group on the axial direction of the Sb atom. The catalyst is recorded as FeSbNC.

2. The method for preparing a semi-metal-doped Fe-based single-atom catalyst according to claim 1, characterized in that The method proceeds as follows:

1. Preparation of ZIF-8 precursor: First, 2-methylimidazole is uniformly dissolved in a methanol solution to obtain a solution A; then zinc nitrate is dissolved in a methanol solution to obtain a solution B; solution B is added to solution A, stirred at room temperature for 20 to 24 hours, and then centrifuged, washed, and dried to obtain a ZIF-8 precursor; 2. Preparation of N-doped porous carbon material: After grinding the ZIF-8 precursor, place it in a tube furnace, heat it to 800-1100°C in an inert atmosphere and keep it for 1-2 hours for heat treatment. After cooling, the N-doped porous carbon material is obtained, which is recorded as NC.

3. Preparation of FeSbNC single-atom catalyst: Fe salt, Sb salt and methanol are fully mixed to obtain solution C; then the N-doped porous carbon material and solution C are evenly mixed, heated and stirred in a water bath until the methanol is completely volatilized, and dried to obtain a precursor; then the precursor is placed in a tubular furnace, heated to 900-1100°C under an inert atmosphere and maintained for 0.5-2.5h for thermal activation, and after cooling, a semi-metal-doped Fe-based single-atom catalyst is obtained.

3. The method for preparing a semi-metal-doped Fe-based single-atom catalyst according to claim 2, characterized in that: The molar ratio of 2-methylimidazole to zinc nitrate in step 1 is (2-4):

1.

4. The method for preparing a semi-metal-doped Fe-based single-atom catalyst according to claim 2 or 3, characterized in that: The heating rate of the tubular furnace described in step 2 is 2 to 10° C. / min.

5. The method for preparing a semi-metal-doped Fe-based single-atom catalyst according to claim 2 or 3, characterized in that: The iron salt described in step 3 is ferric chloride, ferric nitrate or ferric acetylacetonate.

6. The method for preparing a semi-metal-doped Fe-based single-atom catalyst according to claim 2 or 3, characterized in that: The antimony salt described in step 3 is antimony chloride or antimony nitrate.

7. The method for preparing a semi-metal-doped Fe-based single-atom catalyst according to claim 2 or 3, characterized in that: The mass ratio of the antimony salt to the iron salt described in step three is (0.5-2):

1.

8. The method for preparing a semi-metal-doped Fe-based single-atom catalyst according to claim 2 or 3, characterized in that: The mass ratio of the antimony salt to the N-doped porous carbon material described in step three is (0.05-0.4):

1.

9. The method for preparing a semi-metal-doped Fe-based single-atom catalyst according to claim 2 or 3, characterized in that: The water bath heating temperature described in step 3 is 50-70°C.

10. The use of a semi-metal-doped Fe-based single-atom catalyst according to claim 1, characterized in that: The application is to use semi-metal-doped Fe-based single-atom catalysts for the cathode oxygen reduction reaction in proton exchange membrane fuel cells.

Citation Information

Patent Citations

  • Production method of atomically-dispersed metal and nitrogen co-doped carbon-based oxygen reduction reaction catalyst

    CN110013881A

  • Iron / antimony-based heteroatom co-doped carbon nanomaterial as well as preparation method and application thereof

    CN112264065A

  • Preparation method and application of FeSb / NC electrocatalyst

    CN113231093A

  • Nitrogen-doped porous carbon polyhedron loaded bimetallic monatomic oxygen reduction catalyst as well as microwave-assisted preparation method and application thereof

    CN114335573A

  • Preparation method and application of FeSn compound coated NC electrocatalyst

    CN114464821A